Edukasi Hukum untuk Petani Lahan Kering di Desa Tuapukan: Menghindari Kriminalisasi dan Sengketa Tanah - Riwu, Agustin L. M. Rohi; Marthen Dillak; Putu J. A. Lestari (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community service activity was motivated by the high vulnerability of dryland farmers in Tuapukan Village to legal issues, particularly regarding land ownership status and the potential for criminalization. Many farmers still cultivate land without a strong legal basis, such as a certificate or official proof of ownership, which places them in a weak legal position. The objective of this activity was to provide direct legal education to farmers so they understand land rights, land legalization procedures, and efforts to resolve disputes and prevent criminalization. The activity was carried out on July 25, 2025, using counseling methods, group discussions, case simulations, and the distribution of simple agrarian law pocketbooks. The results of the activity indicated an increase in farmers' understanding of land law aspects, as well as a growing collective awareness of the importance of land legality and legal protection. The village government and farmer groups also demonstrated a commitment to follow up on this activity through land data collection and ongoing legal assistance. This activity demonstrates that a community-based educational approach can be an effective strategy in preventing agrarian conflicts and empowering farmers legally.